PERILAKU KOMUNIKASI K-POPERS DALAM INTERAKSI SOSIAL MELALUI APLIKASI V–LIVE VIDEO BROADCASTING (STUDI FENOMENOLOGI K-POPERS DALAM INTERAKSI SOSIAL MELALUI APLIKASI V–LIVE VIDEO BROADCASTING) - Vira Triwiarma; Mohamad Syahriar Sugandi (Derivatif : Jurnal Manajemen, 2018)
V Live app introduced in 2015, V Live app is an app which shows a personal video broadcasting of idol that can be accessed on smartphones as well as other devices such as computers and laptops. This application brings together idol with fans around the world virtually. The purpose of this research is to know what is the motive that underlying K-Popers communication behavior in social interaction through V-Live Video Broadcasting Application and to know how K-Popers communication behavior in social interaction through V-Live Video Broadcasting Application. The research method used is qualitative method by using phenomenology approach. Result of research showed that there is because motive and in order to motive which push informants use V Live application. Then the features in the V Live app help users to explore their relationship with their preferred idols. This happens because of the different interactivity with previous similar applications such as Youtube and Twitter. The feature is a notification, chatroom, and translation that can connect informants virtually with their idols. The implications for communication behavior become more varied verbally and non verbally. One of them is communication between fans with other fans. Verbal behavior of informants with other fans, causing a close relationship between fans. Researchers see that because they have the same idol, fans in the V Live app when writing their comments, they show positive responses to fellow fans. Non-verbal communication shown by informants is kinesics, paralinguistic and proksemic which shows how the feelings of informants when using V Live application. Keywords: Communication Behavior, Social Interaction, K-Popers, Phenomenology, New Media